Elliptic Operators in a Refined Scale of Functional Spaces - Mikhailets, V. A.; Murach, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We study the theory of elliptic boundary-value problems in the refined two-sided scale of the Hormander spaces H^s, φ, where s R,φ is a functional parameter slowly varying on +∞. In the case of the Sobolev spaces H^s, the function φ(|ξ|) 1. We establish that the considered operators possess the properties of the Fredholm operators, and the solutions are globally and locally regular.